The biggest thing in the world - Steven, Kenneth C., 1968- (Lion Children's ; Distributed in the USA by Trafalgar Square Pub., 2010)
"Little Snow Bear had been asleep for 97 and a half days. Now spring time was coming at last. He peeped out of the den to look at the great big world. So Little Snow Bear sets out with his mother for a wonderful day of discovery. Every new thing the little bear sees seems to be bigger than the last. But what is truly the biggest thing in the world?"--Front jacket flap.